Laboratory Diagnosis of a NZ7-like Orf Virus Infection and Pathogen Genetic Characterization, Particularly in the VEGF Gene - Yu, Yongzhong; Duan, Xuyang; Liu, Yuanyuan; Ma, Jinzhu; Song, Baifen; Lian, Zhengxing; Cui, Yudong (Frontiers in Veterinary Science, 2020)
Orf is a widespread contagious epithelial viral disease found particularly in most sheep breeding countries in the world. Recently, an orf virus (ORFV) strain OV-HLJ05 was isolated from an outbreak in northeast China. Three genes of interest including ORFV011 (B2L), ORFV059 (F1L) and ORFV132 (VEGF) of ORFV, were recruited to identify and genetically characterize this newly isolated virus. Compared with the ORFV references listed in GenBank, both B2L and F1L of OV-HLJ05 showed less microheterogeneity from their references. In contrast, the VEGF gene was included in the NZ7-VEGF like group as previously considered by Mercer in 2002. Unexpectedly, further multiple VEGF matches were made, using 34 published sequences from China and India, resulting in 27 strains of the NZ7 members. Based on Karki’s report in 2020, NZ7-VEGF like viruses are emerging more and more frequently in these two countries, damaging the Asian sheep industry. Obvious heterogeneity with the NZ2, insertion of two oligopeptides TATI(L)QVVVAI(L) and SSSS(S) motif were found in the NZ7-like VEGF protein. These VEGFs are divided mainly into two types and a significant increase in the number of hydrogen bonds within the NZ7-like VEGF dimers was observed. The NZ7-like ORFV apparently favors the goat as a host and an emphasis on this in future epidemiological and pathological studies should be considered, focusing on the NZ7-like virus.